Manajemen Persediaan Green bean Sebagai Bahan Baku Kopi Untuk Memenuhi Kebutuhan Konsumen (Studi Kasus pada KTH Giri Senang Kabupaten Bandung) - Marshell, Christhoper; Trimo, Lucyana; Tridakusumah, Ahmad Choibar; Pardian, Pandi (Universitas Galuh, 2024)
KTH Giri Senang is one of the largest coffee production centers in Cilengkrang District, Bandung Regency. However, the inventory management of green beans at KTH Giri Senang is still inefficient, often experiencing shortages. This study aims to analyze how the inventory management of green beans at KTH Giri Senang can be optimized. The methods used in this study include Economic Order Quantity (EOQ), Reorder Point, safety stock, and total inventory cost. This research employs a case study method with a qualitative approach, and data collection techniques include observation, interviews, and documentation. Based on the research results, the calculations are as follows: EOQ is 54,068 kg, optimal ordering frequency is 2 times per year, total inventory cost is Rp. 9,830,614, safety stock is 1,902 kg, and Reorder Point is 3,002 kg. However, KTH Giri Senang cannot directly implement the EOQ method calculations due to capital constraints. Therefore, KTH needs to improve cash flow, increase sales and marketing, expand partnership networks, and provide training to members on inventory management. The implementation of these strategies is expected to help KTH Giri Senang address inventory management issues, allowing coffee production operations to run more efficiently and reducing the risk of green bean shortages in the future.